Pengaruh Besaran Pendapatan Terhadap Tingkat Kepatuhan Peserta JKN Mandiri dalam Membayar Iuaran JJK di Kelurahan Pacitan - Inten Simbareja; Anak Agung Istri Citra Dewiyani (Poltekkes Kemenkes Malang, 2020)
National Health Insurance or JKN is a government program implemented to meet the needs of the Indonesian people in the health sector. JKN is organized by BPJS Kesehatan which has many problems, such as deficit. One of the causes of the high deficit rate is the low compliance of JKN participants in the independent segment in paying contributions. This research is a quantitative analytic with cross sectional approach. This study aims to determine the description of the level of income of respondents and the level of compliance of respondents and to know there is a correlation between income and compliance of JKN participation in paying JKN contribution. Respondents in this study are 89 people. 60.7 percent of the total respondents had a high level of income categorized, and 39.3 percent had a low level of income. And 49.4 percent of respondents complied in paying JKN contributions, 50.6 percent the rest were not compliant in paying JKN contributions. Based on the Chi Square test results found that the p value equal 0.000 lower than p. So H0 is rejected, which means the amount of the income level has a correlation with level of compliance of JKN participation in paying JKN contribution.